(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2026)
Background: Rehabilitation is a core component of universal health coverage, yet it remains inadequately integrated into primary healthcare systems in many low- and middle-income countries, limiting early intervention, functional recovery, and long-term quality of life. This study aims to explore global models and innovative strategies for strengthening the integration of rehabilitation into primary healthcare in Bangladesh to inform context-appropriate policy and service reforms. Methods: A narrative review was conducted using a structured literature search of major bibliographic databases (Sciverse Scopus, PubMed, Embase, Web of Science, and Cochrane Library) and World Health Organization institutional repositories for literature published between 2014 and 2025. The search terms covered rehabilitation integration, primary healthcare, health system strengthening, and technological innovations. Studies from global and low- and middle-income countries were prioritised. Study selection and screening followed a structured selection process, and the included studies were thematically synthesized to develop a context-specific framework for Bangladesh. Results: Physical disabilities represent a significant share of rehabilitation needs; however, access to and the quality of available rehabilitation services remain limited. In Bangladesh, service provision is primarily influenced by three factors: inadequate physical infrastructure, shortages of trained personnel, and insufficient financing, which contribute to the concentration of services in urban areas. Although community-based rehabilitation initiatives have demonstrated improved service reach and acceptability, the integration of physical and mental health rehabilitation within primary healthcare remains limited. International experiences, including Chile’s comprehensive rehabilitation system and selected models from the Brazil, Russia, India, China, South Africa countries, highlight effective approaches to integrating rehabilitation into primary healthcare. Technological applications, particularly telerehabilitation and other low-cost digital platforms, have the potential to expand access to services. Conclusion: Strengthening rehabilitation in Bangladesh’s primary health care requires integrating basic services, training health workers, and establishing referral pathways, alongside expanding low-cost digital and community-based care to improve access in underserved areas.